(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Companies are currently involved in projects that are crucial to their performance as a result of market globalization and internationalization, which has increased competitive demands on businesses. These projects must be managed, planned, organized, staffed, monitored, controlled, and assessed in order to be successful. Primavera, a project management system, is a complete solution for professionally managing projects. This article gives an example of how to manage a project and allocation of resources using the Primavera software. One of the most critical management jobs is resource allocation, which enables strategy implementation. In businesses where strategic management is not practiced, resources are distributed based on personal or political considerations. However, in strategy-based companies, resources are allocated based on annual targets’ priority. Failure to link executive plans and determine the priority in assigning resources to strategic long-term projects is one of the primary challenges to successful organisation strategy implementation. In order to achieve organisational goals, any organisation must allocate at least four types of resources. These resources include financial, physical, human, and technological resources.